Aplikasi Layanan Antarjemput XYZ Berbasis Android - Gosal, Robert; Andjarwirawan, Justinus; Handojo, Andreas (Jurnal Infra, 2016)
XYZ Shuttle service is a company that works in transportation service area and also one of the alternative transportations that can be used to pick and drop people to their destinations. XYZ Shuttle Service is shuttle service which have 2 types of services, one is request service where the user can order the shuttle to pick them up according to the address requested and will take the user to the requested destination address. The other service are regular service where the user will be picked up and delivered every day based from the order. One of the shuttle service company is XYZ shuttle service. Now, XYZ shuttle service still keep the order record in manual system, where the user is still using telephone to order the service. Because of that, sometimes the order record is not too accurate. Therefore, it need an information system to help and reduce the weaknesses of the manual system.This application of XYZ shuttle service based on Android is intended to help the user can order the shuttle service more easy and faster. This application will be built using HTML, Javascript, PHP language which will be converted into mobile application using Eclipse. This mobile application will also help user to identify the driver who will pick-up the user. It will help facilitate the pick-up process. Besides being able to assist in order shuttle service, this application also helps shuttle service company to record and process the order more quickly and accurately so it will help in the pick-up process. The manual system analysis process is conducted by survey to shuttle services.Based on test results, this application run well on some devices such as Android 4.2 (Jelly Bean), Android 4.4 (Kitkat). The application can run the order service function, send the notification, view the order data, and display driver identity so make user to obtain information about the driver is run pretty well.